Shopping for Health: A Menu for One - Morgan Denhard; Wendy Dahl (EDIS)
In today’s busy world, many Americans find themselves cooking meals for one. Older adults and college students alike face the challenge of making meal preparation a priority when no one else is depending on them to create a balanced meal. Whether you pop a dish into the microwave after a busy day or spend time cooking a special meal for yourself, shopping for and preparing healthy, low-cost meals for one can be easy and enjoyable with just a little bit of planning. This 4-page fact sheet was written by Morgan Denhard and Wendy Dahl and published by the UF Department of Food Science and Human Nutrition, February 2013.